Challenging Experience with Severe Complicated Malaria in the City of Dhaka (Journal of Medicine, 2022)
Malaria is a vector-borne febrile illness that requires an association of three factors- parasite, vector, andhost- to continue its life cycle. The physical and cultural environments, as rainfall, humidity, and temperaturepermitted Bangladesh to be a malaria-endemic area, where Plasmodium falciparum is the dominantparasite and accounts for 93% of the malaria cases in the country. Due to the high degree of severity of thedisease and about 15% of total annual deaths in Bangladesh, in the year of 1961, Malaria EradicationProgram (MEP) was introduced. NMEP caused a significant reduction in total malaria incidences, severityand deaths. Still 33.6% of the total population in Bangladesh is at risk of malaria and the majority of casesare reported in 13 endemic areas of 64 districts in the country. Above all, resurgence of malaria andtreatment resistant cases have become a burning issue to think about in recent years. Here, we presenttwo severe falciparum malaria cases that challenged us with the complicated nature of the disease inDhaka city, which is not listed as a malaria endemic zone of Bangladesh.J MEDICINE 2022; 23: 87-95